Clinical and laboratory characterization of 114 cases of Castleman disease patients from a single centre: paraneoplastic pemphigus is an unfavourable prognostic factor. (30th March 2015) - Dong, Yujun; Wang, Mingyue; Nong, Lin; Wang, Lihong; Cen, Xinan; Liu, Wei; Zhu, Sainan; Sun, Yuhua; Liang, Zeyin; Li, Yuan; Ou, Jinping; Qiu, Zhixiang; et al.
Summary This study retrospectively collected the clinical and laboratory data of 114 patients with Castleman disease (CD) from a single medical centre. Clinical classification identified 62 patients (54·4%) with unicentric Castleman disease and 52 (45·6%) with multi‐centric Castleman disease. Pathological classification revealed 68 cases (59·6%) of hyaline vascular variant, 16 (14·1%) mixed cellular variant (Mix) and 30 (26·3%) plasmacytic variant. Clinical complications occurred in 69 CD patients, including 37 cases of paraneoplastic pemphigus (PNP) and 25 cases with renal complications. Haematological involvement, pleural effusion and/or ascites and POEMS syndrome (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin changes) were also found. Univariate analysis showed that presence of clinical complications and PNP were both risk factors relating to CD patient survival. Prognostic factors showing P < 0·15 in univariate analysis and those with clinical significance were subjected to multivariate analysis using a Cox regression model. PNP presence and age over 40 years both significantly adversely affected survival. Thus, only presence of PNP was identified as an independent unfavourable survival risk factor in both univariate and multivariate analyses. Overall, the present data provide a panoramic description of CD cases and emphasize that the presence of PNP is an adverse prognostic factor.